Intergranular crack nucleation in polycrystalline alumina - Aswad, M; Marrow, T (2010)
Crack nuclei in pure and Cr-doped aluminas with average grain size between 1.5 μm and 3.6 μm have been studied using digital image correlation of optical images, to observe the interaction between microstructure, residual stress and damage development. Individual intergranular crack nuclei within areas comprising tens of thousands of grains were studied to measure crack surface lengths and crack opening displacements as a function of load, prior to unstable fracture. Grain orientations in the vicinity of intergranular crack nuclei, and the grain boundary planes, has been characterised by trace analysis and electron backscatter diffraction. This allows estimation of the thermal stresses that were sufficient to crack the grain boundaries.